2015
DOI: 10.1002/jcb.25133
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivation of Akt1/GSK3β Isoform‐Specific Signaling Axis Promotes Pancreatic β‐Cell Regeneration

Abstract: Promotion of insulin-secreting β-cell regeneration in patients with diabetes is a promising approach for diabetes therapy, which can contribute to rescue the uncontrolled hyperglycemia. Low-power laser irradiation (LPLI) has been demonstrated to regulate multiple physiological processes both in vitro and in vivo through activation of various signaling pathways. In the present study, we showed that LPLI promoted β-cell replication and cell cycle progression through activation of Akt1/GSK3β isoform-specific sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
0
6
0
2
Order By: Relevance
“…GSK3 has been demonstrated to be a downstream target of multiple signaling pathways and is associated with cell proliferation and cell cycle regulation ( 17 ). It has been reported that stimulation of GSK3 negatively regulates β-cell function by maintaining the sub-cellular localization and stability of Pdx1 ( 18 ).…”
Section: Insulin Signaling Pathwaysmentioning
confidence: 99%
“…GSK3 has been demonstrated to be a downstream target of multiple signaling pathways and is associated with cell proliferation and cell cycle regulation ( 17 ). It has been reported that stimulation of GSK3 negatively regulates β-cell function by maintaining the sub-cellular localization and stability of Pdx1 ( 18 ).…”
Section: Insulin Signaling Pathwaysmentioning
confidence: 99%
“…The STRING database was applied to perform PPI network analysis on the 51 selected intersected targets, among which the top 3 targets of degree were AKT1, CASP3, and IL6. AKT1, a member of the serine/tyrosine family, is a critical downstream molecule in the PI3K/AKT/mTOR pathway, and is involved in significant immune pathways such as cytokine activation [ 30 ]. An existing report unveiled that the deletion of AKT1 accelerated kidney fibrosis through the activation of TGF-β1/STAT3 signaling in a mouse model of unilateral ureteral obstruction (UUO) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…LPLI suppresses tumor growth and induces apoptosis in ASTC-a-1 human lung adenocarcinoma cells [ 7 ]. These results demonstrate that the antitumor effects of LPLI treatment involve in the induction of apoptosis [ 8 , 9 ], which is the preferred way to manage cancer.…”
Section: Introductionmentioning
confidence: 93%